Out of the box, into the world: the contribution of archives and archivists to today's world. Issue 1 (January 2018) - Hocking, John; Biagioni, Chiara
Abstract : This is a piece about the global importance of archives and archivists. From the Global Seed Vault in Svalbard, near the North Pole, that helped fight hunger in the war in Syria to the archives of Australia that have assisted thousands of victims of the "Stolen Generations" reclaim their identity, this piece shows how archivists help tackle global issues in today's interconnected society. Recalling the heroic acts of the custodian of the legendary manuscripts of Timbuktu, as the city was besieged by rebels and extremists, the authors challenge archivists to explore how far they would go to protect archives and preserve them for humanity. Finally, partnerships and cooperation both within and outside the archival world are discussed, emphasising that the "possibilities are endless" when archivists bring the archives "out of the box and into the world".